Tradisi Hasil Panen Raya Sawah Yang Diadakan Setiap Satu Tahun Sekali Didesa Penutuk, Kecamatan Lepar - Ilham Ilham; Dimas Syanjaya; Rani Rani; Sulis Margareza; Elisa Melani; Heldi Apriansyah; Lidya Yulinda Putri; Ola Ostarika; Rajawijaya Rajawijaya; Ardi Dwi Pratama; Dea Mulya Sukma; Ari Juliansyah; Ratno Purnama Sari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The Grand Harvest tradition in Penutuk Village, Lepar District, is an annual celebration that is rich in meaning and cultural value. As an expression of gratitude for the abundant harvest from the rice fields, this event becomes a social glue that strengthens ties between residents. More than just a harvest celebration, this tradition reflects the noble values ​​of the Penutuk Village community, such as togetherness, mutual cooperation, and preserving local culture that has been passed down from generation to generation. The series of events which took place on January 19 2025 involved all levels of society, from children to the elderly, with active participation in each procession. This article will examine in depth the philosophical meaning behind this tradition, describing in detail the series of events which include traditional ceremonies and social activities. Apart from that, this article will also discuss efforts to preserve the harvest tradition in Penutuk Village so that it remains sustainable and can be passed on to future generations, including adaptation strategies to changing times and the challenges of modernization. It is hoped that this research can contribute to a more comprehensive understanding of the importance of preserving local culture in Indonesia, especially in the context of agriculture and the social life of rural communities. Thus, this article does not only describe a tradition, but also offers a broader perspective on the social, economic, and cultural values ​​contained therein.